PERBANDINGAN PRESTASI BELAJAR SISWA DENGAN PENDEKATAN PBL DAN KONTEKSTUAL PADA POKOK BAHASAN OPERASI BILANGAN BULAT DITINJAU DARI MOTIVASI SISWA KELAS V SD NEGERI DI KECAMATAN DANDER BOJONEGORO TAHUN AJARAN 2016/2017 - Nur Rohman (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2016)
The purpose of this research is to determine: (1) Which gives better performance between learning with Contextual approach, direct or PBL learning. (2) Which gives better performance between learning motivation high, medium or low. (3) At the motivation high, medium and low, which one gives better performance among learning with Contextual approach, direct or PBL learning. This study is a quasi-experimental research with a 3 x 3 factorial design. Population Elementary School fifth grade students throughout the District Bojonegoro Dander academic year 2016/2017. Hypothesis testing using two-way analysis of variance with different cells. Conclusion: (1) The achievement of mathematics learning that using model PBL approach is better than the Contextual and direct instructional model, and mathematics achievement of students using model approach Contextual better than models direct learning. (2) The learning achievement of mathematics learning motivation high is better than being motivated and low motivation, and achievement motivation to learn mathematics by being better than low motivation. (3) In terms of motivation, mathematics achievement of students who use the learning model PBL approach is better than the Contextual and direct instructional model, and mathematics achievement of students using model approach Contextual better than direct instructional model